The First Oration of the Nepal Orthopaedic Association Challenges of an Orthopaedic Surgeon in Nepal - Banskota, Ashok Kumar (Nepal Orthopaedic Association Journal, 2013)
DOI: http://dx.doi.org/10.3126/noaj.v1i1.8125 Nepal Orthopaedic Association Journal Vol.1(1) 2010